Implementation of The Pancasila Learner Profile (P5) Strengthening Project for PDBK at SD Negeri Minggiran Yogyakarta - Dono, Pusrayan; Faiz Noormiyanto (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This research aims to describe the implementation of the Pancasila Student Profile Strengthening Program (P5) for Learners with Special Needs (PDBK) at SD Negeri Minggiran Yogyakarta. The research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of P5 has accommodated the active involvement of PDBK through inclusive, adaptive, and collaborative approaches. The six dimensions of P5: faith and piety in God Almighty, global diversity, mutual cooperation, independence, critical reasoning, and creativity are implemented thematically and contextually, with adjustments to the characteristics of PDBK, especially slow learners. Teachers and Special Education Teachers (GPK) play an important role in the learning process and character strengthening. However, the implementation of P5 still faces obstacles such as limited teacher competence in inclusive education, the limited number of GPKs, and the lack of appropriate learning media. This study concludes that P5 can be effectively implemented for PDBK if supported by cross-party collaboration, appropriate learning strategies, and school policies that support equitable and diversity-friendly education. Keywords: Pancasila Learner Profile, Learners with Special Needs, Slow Learner, Inclusive Education, Merdeka Curriculum